Role of Happiness: Mediating Digital Technology and Job Performance Among Lecturers - Bangun, Yuni Ros; Pritasari, Adita; Widjaja, Fransisca Budyanto; Wirawan, Christina; Wisesa, Anggara; Ginting, Henndy (Frontiers in Psychology, 2021)
Purpose Happiness has been the most important goal for humans throughout history and is a significant issue among university lecturers facing a rapid digital technology change. It is usually described as a well-being state, feeling satisfied and contented, consisting of positive happenings in an individual’s life concerning the social, spiritual, economic, psychological, and physiological spheres. This research examines the relationship between happiness, attitudes toward technology, and lecturers’ job performance in higher education. Design and Methodology This research design was a cross-sectional design that asked the respondents from lecturers of Institut Teknologi Bandung, one of the best universities with technology-based education in Indonesia, to complete a group of well-validated questionnaires. The questionnaires mentioned earlier include the Oxford Happiness Questionnaire and three other newly constructed questionnaires, made to measure attitude toward digital technology, job satisfaction, and job performance. Findings This research confirmed that happiness fully mediated the relationship between attitude toward digital technology and job performance. Additionally, this research also confirmed that happiness partially mediated the relationship between job satisfaction and job performance. These results implied that a positive attitude toward digital technology and higher job satisfaction would lead to happier lecturers who increase their job performance. Originality This study suggests that a positive attitude toward technology has a higher impact than job satisfaction as determinant factors of happiness and its association with lecturers’ job performance such as universities, especially Institut Teknologi Bandung as a technologically advanced workplace environment. Additionally, the Oxford Happiness Questionnaire framework, frequently used in studies of other countries, is now being used in the context of an Indonesian case study, precisely to measure happiness among lecturers in Indonesian higher education.